2020
DOI: 10.20546/ijcrbp.2020.708.001
|View full text |Cite
|
Sign up to set email alerts
|

Response of seven tomato (Lycopersicon esculentum Mill.) cultivars produced in Benin to salinity stress at young plant stage

Abstract: In this study, we evaluated the salt resistance level of seven tomato cultivars Akikon, Tounvi, Thorgal, F1 Mongal, Padma, Petomech and TLCV15 at young plant stage. The experiment was laid out as a Randomized Complete Design (RCD) with four replications in a greenhouse. Three-week old plants from the seven cultivars were submitted in pots containing a mixture of potting soil and sand to five NaCl concentrations: 0; 30; 60; 90 and 120 mM NaCl corresponding respectively to an electric conductivity of 0.221; 3.82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…As for other plants species, salt stress reduces tomato plants' growth [16,17]. Studies in the Republic of Benin have shown that several tomato cultivars produced in the country undergo significant reductions in growth under NaCl salt stress [8]. It is well known that improving a plant's tolerance to salinity can be achieved, in addition to genetic selection, through the use of suitable physiological tools [18].…”
Section: Tomatomentioning
confidence: 99%
See 2 more Smart Citations
“…As for other plants species, salt stress reduces tomato plants' growth [16,17]. Studies in the Republic of Benin have shown that several tomato cultivars produced in the country undergo significant reductions in growth under NaCl salt stress [8]. It is well known that improving a plant's tolerance to salinity can be achieved, in addition to genetic selection, through the use of suitable physiological tools [18].…”
Section: Tomatomentioning
confidence: 99%
“…Day/night mean temperatures were 26°C/23°C with a mean humidity of 55%. The experiment was conducted as described by Kinsou et al [8] with three plants per pot. Four treatments were used consisting in watering the plants every other day with 200 ml / pot of 0 mM (Control: C); 120 mM NaCl (Salt: S); 120 mM NaCl + 40 mM CaSO 4 (S + CaSO 4 ) and 120 mM NaCl + 40 mM Ca(NO 3 ) 2 (S + Ca(NO 3 ) 2 ).…”
Section: Experimental Design and Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is variability among cultivars relatively to their response to salinity. It is well known in plants that there is substantial variation in resistance to salinity among cultivars of the same species (Gandonou et al, 2012;Wouyou et al, 2017;Kpinkoun et al, 2019;Kinsou et al, 2020).…”
Section: Salt Resistance Of the 7 Cultivarsmentioning
confidence: 99%
“…Salinity is one of the most important environmental constraints limiting plant productivity around the world (Ashraf and Harris, 2004). Although most of the cultivated plants are glycophyte species, their overall responses to increasing NaCl do appear to be species-specific (Lutts et al, 1995;Wouyou et al, 2017;Kpinkoun et al, 2019;Kinsou et al, 2020). Moreover, within a given species, a substantial variation in salt sensitivity may occur among cultivars (Ould Mohandi et al, 2011;Manaa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%